The dollhouse murders - Wright, Betty Ren. (New York : Holiday House, 1983)
A dollhouse filled with a ghostly light in the middle of the night and dolls that have moved from where she last left them lead Amy and her retarded sister to unravel the mystery surrounding grisly murders that took place years ago.
13 18 20 38
Keywords: Dolls -- Fiction; Mystery and detective stories; Mentally handicapped -- Fiction; Sisters -- Fiction; Dollhouses -- Fiction